High-performance all-solid-state sodium ion battery and preparation method thereof

By using NASICON solid electrolyte and Prussian white positive electrode materials in sodium ion batteries, combined with metal sodium negative electrodes, the problem of insufficient safety and specific energy of existing sodium ion batteries is solved, and a full solid state with high safety and high specific energy is achieved Sodium ion battery.

CN119481231APending Publication Date: 2025-02-18ANHUI UNIV
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411623818.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing sodium ion batteries have problems of low safety and insufficient specific energy, especially when using organic liquid electrolytes, there is a risk of spontaneous combustion and leakage.

Method used

The battery module is prepared by using an all-solid-state battery structure, using NASICON solid electrolyte and Prussian white positive electrode material, combined with a sodium metal negative electrode, and a battery module is prepared by co-precipitation method and high-temperature solid-phase sintering method to reduce the crystallization water content and improve interface stability.

Benefits of technology

It has achieved a full-solid-state sodium ion battery with high safety and high specific energy, with excellent electrochemical performance and long cycle performance at room temperature, and has the potential for commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481231A_ABST
    Figure CN119481231A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance all-solid-state sodium ion battery, and belongs to the technical field of power batteries, the sodium ion battery comprises a Prussian white positive electrode, a metal sodium negative electrode and an NASICON type solid electrolyte; preparation raw materials of the Prussian white positive electrode comprise Prussian white, the general formula of the Prussian white is NaxFe [Fe (CN) 6], and x is larger than or equal to 1.8 and smaller than 2.2; the composition of the NASICON type solid electrolyte is NaxZr2-yMySiuPvO12, x is more than 0 and less than or equal to 4, y is more than or equal to 0 and less than 2, u is more than 0 and v is less than 3; in the NaxZr2-yMySiuPvO12, M is at least one of a Zn element, a Mg element, a Cu element, an Al element, a Ni element, a Ga element, a Fe element and a K element. The sodium ion battery has excellent electrochemical performance at room temperature, is high in safety, and is beneficial to commercialized development and application of all-solid-state sodium ion batteries. The invention also provides a preparation method of the high-performance all-solid-state sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of power batteries, and in particular relates to a high-performance all-solid-state sodium ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have been widely used in portable electronic devices and electric vehicles due to their high energy density, long cycle life, and high portability. However, lithium resources are relatively scarce and cannot meet the growing energy market demand. The high cost of battery manufacturing limits its application in large-scale energy storage. It is crucial to develop high-performance and low-cost secondary batteries. Sodium-ion batteries have the advantages of low cost and wide distribution of resources. They have great potential in energy density, cycle life, and environmental friendliness. Metallic sodium is safer than metallic lithium and metallic potassium. At present, industrialized or commercialized sodium-ion batteries use organic liquid electrolytes, which are not safe, have insufficient specific energy, and have safety issues associated with thermal runaway. There is a possibility of leakage and combustion during battery use. The development of solid-state sodium batteries and the use of solid electrolytes instead of traditional liquid electrolytes can effectively solve the problem of spontaneous combustion of traditional liquid batteries. Therefore, it is still necessary to develop high-safety and high-specific-energy all-solid-state batteries. NASICON-type oxide solid electrolytes have the advantages of high room temperature ionic conductivity, high thermal stability and chemical stability, easy preparation and synthesis, and cheap raw materials. Their dense morphology gives them higher mechanical strength and the ability to withstand high voltages, making them extremely promising for application.

[0003] The cathode materials of sodium ion batteries usually use transition metal oxides, polyanion compounds and Prussian blue analogs. Transition metal oxides are prone to irreversible phase transitions; polyanion compounds have good structural stability and capacity retention, but their discharge capacity is not ideal. Prussian blue analogs have low raw material costs, high operating voltage windows and reversible capacity. Among them, Prussian white has a high theoretical capacity (up to 170 mAh g) as a cathode material for sodium ion batteries. -1 ), low raw material prices and scalable preparation, it has good prospects in industrial production and large-scale energy storage technology. Prussian white material has two active sites, which can undergo two-electron redox reactions. Its stable three-dimensional framework structure and large gap are conducive to the realization of Na + Reversible storage and rapid deintercalation achieve low lattice tension and fast ion diffusion dynamics. However, crystal water is inevitably introduced into the lattice of Prussian white materials. If sodium-ion batteries use organic electrolytes, the presence of crystal water will cause battery capacity loss. In addition, the interface formed by Prussian white and the electrolyte is unstable, which will cause the sodium-ion battery to be unable to achieve stable long-term circulation, hindering its practical application. Summary of the invention

[0004] In order to solve the problems of low safety and low specific energy of existing sodium ion batteries, the present invention provides a high-performance all-solid-state sodium ion battery, which has excellent electrochemical properties at room temperature and high safety, and is conducive to the commercial development and application of all-solid-state sodium ion batteries.

[0005] The present invention also provides a method for preparing a high-performance all-solid-state sodium ion battery.

[0006] The present invention is achieved through the following technical solutions:

[0007] The present invention provides a high-performance all-solid-state sodium ion battery, wherein the sodium ion battery comprises a Prussian white positive electrode, a metallic sodium negative electrode and a NASICON solid electrolyte;

[0008] The raw material for preparing the Prussian white positive electrode comprises Prussian white, and the general formula of the Prussian white is: Na x Fe[Fe(CN)6], where 1.8≤x<2.2;

[0009] The composition of the NASICON solid electrolyte is Na x Zr 2-y M y Si u P v O 12 , where 0<x≤4, 0≤y<2, 0<u, v<3;

[0010] The Na x Zr 2-y M y Si u P v O 12 Here, M is at least one of Zn element, Mg element, Cu element, Al element, Ni element, Ga element, Fe element and K element.

[0011] Furthermore, the raw materials for preparing the Prussian white positive electrode also include a conductive agent, a binder and a high ion conductivity solid electrolyte;

[0012] The mass ratio of the Prussian white, the conductive agent, the binder and the high ion conductivity solid electrolyte is (70-80): (5-10): (5-20): (5-10).

[0013] Further, the conductive agent includes at least one of acetylene black, Ketjen black, carbon black, vapor-grown carbon fiber and carbon nanotubes;

[0014] The binder comprises at least one of polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene and sodium hydroxymethyl cellulose;

[0015] The high ionic conductivity solid electrolyte includes Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 and Na 3.4 Zr 1.8 Cu 0.2 Si2PO 12 Any one of .

[0016] Based on the same inventive concept, the present invention provides a method for preparing a high-performance all-solid-state sodium ion battery, the preparation method comprising:

[0017] Prussian white was synthesized by coprecipitation method;

[0018] The Prussian white, conductive agent, binder and high ion conductivity solid electrolyte are dispersed in a solvent, coated on a current collector after grinding, and then dried to obtain a Prussian white positive electrode;

[0019] Sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide are mixed and ball-milled, and the obtained slurry is dried and calcined to obtain a precursor powder;

[0020] The precursor powder is ball-milled and dried, and then tableted and calcined to obtain a NASICON solid electrolyte;

[0021] The Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery.

[0022] Furthermore, the synthesis of Prussian white by coprecipitation method specifically includes:

[0023] Dissolve sodium ferrocyanide in water to obtain solution A;

[0024] A soluble divalent transition metal salt is dissolved in water, and then a chelating agent is added to obtain a solution B;

[0025] Mixing the solution A and the solution B to perform a coprecipitation reaction to obtain a reaction solution;

[0026] The reaction liquid is subjected to solid-liquid separation, and the obtained solid is washed and dried to obtain Prussian white.

[0027] Furthermore, the soluble divalent transition metal includes ferrous salt, and the chelating agent includes sodium citrate.

[0028] Furthermore, the Prussian white, conductive agent, binder and high ion conductivity solid electrolyte are dispersed in a solvent, coated on a current collector after grinding, and then dried to obtain a Prussian white positive electrode, which specifically includes:

[0029] The Prussian white, conductive agent, binder and high ion conductivity solid electrolyte are dispersed in N-methylpyrrolidone, ground evenly and coated on a current collector, and then dried to obtain a Prussian white positive electrode;

[0030] Wherein, the mass ratio of the Prussian white, the conductive agent, the binder and the high ion conductivity solid electrolyte is (70-80): (5-10): (5-20): (5-10);

[0031] The current collector comprises at least one of copper foil, aluminum foil, Al@C foil, titanium foil and stainless steel;

[0032] The conductive agent comprises at least one of acetylene black, Ketjen black, carbon black, vapor-grown carbon fiber and carbon nanotube;

[0033] The binder comprises at least one of polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene and sodium hydroxymethyl cellulose;

[0034] The high ionic conductivity solid electrolyte includes Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 and Na 3.4 Zr 1.8 Cu 0.2 Si2PO 12 Any one of .

[0035] Furthermore, the sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide are mixed and ball-milled, and the obtained slurry is dried and calcined to obtain the precursor powder, which specifically includes:

[0036] Sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide are mixed and wet-milled with alcohol as the medium. The obtained slurry is dried and calcined at 1050-1200° C. for 7-10 hours to obtain a precursor powder.

[0037] Wherein, the molar ratio of the sodium carbonate, the zirconium dioxide, the silicon dioxide, the phosphate and the metal oxide is (3-4): (1.5-2): (1.8-2.5): (0.5-1.2): (0.1-0.4).

[0038] Furthermore, the precursor powder is ball-milled and dried, and then pressed and calcined to obtain a NASICON solid electrolyte, which specifically includes:

[0039] The precursor powder is ball-milled to a particle size of 1 to 5 μm, dried, pressed into sheets, and then calcined at 1050 to 1200° C. for 7 to 10 hours to obtain a NASICON solid electrolyte;

[0040] Wherein, the diameter of the NASICON type solid electrolyte is 6 to 15 mm, and the thickness is 0.6 to 2 mm.

[0041] Furthermore, the Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery, which specifically includes:

[0042] The Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery, and the metallic sodium negative electrode is preheated to 100±15°C.

[0043] Furthermore, the diameter of the metallic sodium negative electrode is 8 to 12 mm, and the thickness is 0.5 to 1.8 mm.

[0044] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0045] 1. The present invention discloses a high-performance all-solid-state sodium ion battery, which is assembled by a Prussian white positive electrode, a metallic sodium negative electrode and a NASICON solid electrolyte, wherein the composition of the NASICON solid electrolyte is Na x Zr 2- y M y Si u P v O 12 , by doping metal elements to reduce the pores of the solid electrolyte and improve the Na + concentration, regulates the grain boundary composition, reduces the interface impedance, and significantly improves the grain boundary ion conductivity of the solid electrolyte, thereby improving the overall ion conductivity of the NASICON solid electrolyte. The Prussian white positive electrode has a stable three-dimensional open framework structure formed by coordination, which can realize Na +Stable and reversible insertion and extraction, in coordination with the NASICON solid electrolyte with high room temperature ionic conductivity and the metallic sodium negative electrode, effectively improve the electrochemical performance of the all-solid-state sodium ion battery at room temperature. The room temperature ionic conductivity of the NASICON solid electrolyte of the present invention reaches 1.5mS / cm, the electrochemical window is 5.2V, and the capacity of the all-solid-state sodium ion battery assembled with the Prussian white positive electrode and the metallic sodium negative electrode can reach 119mAh g -1 , and exhibits excellent long-cycle performance, with potential for commercial application.

[0046] 2. The present invention provides a high-performance all-solid-state sodium ion battery, which is assembled by a Prussian white positive electrode, a metallic sodium negative electrode and a NASICON solid electrolyte. The Prussian white positive electrode itself has few defect vacancies and a low content of crystal water, and the NASICON solid electrolyte will not introduce crystal water into the Prussian white positive electrode, thereby avoiding the presence of crystal water causing battery capacity loss. The interface formed between the NASICON solid electrolyte and the Prussian white positive electrode has high stability, which is conducive to the stable long-term circulation of the sodium ion battery.

[0047] 3. The present invention provides a method for preparing a high-performance all-solid-state sodium ion battery, wherein the method adopts a high-temperature solid-phase sintering method to prepare a NASICON-type solid electrolyte Na doped with a metal element. x Zr 2-y M y Si u P v O 12 The NASICON-type solid electrolyte has high ionic conductivity at room temperature. The nucleation and growth process of Prussian white is regulated by adding a chelating agent to reduce its defect vacancies and crystal water content. An effective method for supporting the use of Prussian white positive electrode materials in sodium ion batteries is proposed, which improves the electrochemical performance of solid-state sodium ion batteries at room temperature, and improves their stability and safety, which is conducive to the commercial development and application of all-solid-state sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0049] Figure 1 The Prussian white X-ray diffraction pattern (left) and scanning electron microscope image (right) obtained in Example 1;

[0050] Figure 2 The Na obtained in Example 13.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 X-ray diffraction pattern (left) and actual image of solid electrolyte (right);

[0051] Figure 3 Example 1 Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 SEM image of solid electrolyte;

[0052] Figure 4 Schematic diagram of the structure of all-solid-state batteries prepared in Example 1, Example 2 and Example 3;

[0053] Figure 5 is Na in Example 1 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 Impedance spectrum (left) and linear sweep voltammetry curve (right) of the solid electrolyte;

[0054] Figure 6 The charge and discharge curves of the all-solid-state batteries prepared in Example 1 and Example 2 are shown.

[0055] Figure 7 This is the cycle performance diagram of the all-solid-state battery prepared in Example 1. DETAILED DESCRIPTION

[0056] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0057] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0058] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0059] The technical principles of the present invention are as follows:

[0060] In order to overcome the problems of high defect concentration, high crystal water content, electrolyte matching and interface optimization in the existing Prussian white positive electrode materials, the present invention not only provides a NASICON type solid electrolyte with high ionic conductivity at room temperature, but also reduces the pores of the solid electrolyte by doping metal elements to improve the Na + The concentration is adjusted, the grain boundary composition is regulated, the interface impedance is reduced, and the grain boundary ion conductivity of the solid electrolyte is significantly improved, thereby improving the overall ionic conductivity of the NASICON solid electrolyte. In addition, an effective method to support the application of Prussian white positive electrode materials in sodium ion batteries is proposed. By regulating the nucleation and growth process of Prussian white, a Prussian white positive electrode material with few defect vacancies and low crystal water content is obtained. The NASICON solid electrolyte with high room temperature ionic conductivity and metallic sodium are coordinated to improve the electrochemical performance of sodium ion all-solid-state batteries at room temperature, which is of great application value. Among them, the prepared Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The room temperature ionic conductivity of the solid electrolyte reaches 1.5 mS / cm, the electrochemical window is 5.2 V, and the capacity of the all-solid-state sodium-ion battery assembled with Prussian white material (PW) as the positive electrode material and sodium metal as the negative electrode material can reach 119 mAh g -1 , and exhibits excellent long-cycle performance, with potential for commercial application.

[0061] The present invention discloses a high-performance all-solid-state sodium ion battery, comprising a Prussian white positive electrode, a metallic sodium negative electrode and a NASICON solid electrolyte;

[0062] The raw material for preparing the Prussian white positive electrode comprises Prussian white, and the general formula of the Prussian white is: Na x Fe[Fe(CN)6], where 1.8≤x<2.2;

[0063] The composition of the NASICON solid electrolyte is Na x Zr 2-y M y Si u P v O 12 , where 0<x≤4, 0≤y<2, 0<u, v<3;

[0064] The Na x Zr 2-y M y Si u P v O 12Here, M is at least one of Zn element, Mg element, Cu element, Al element, Ni element, Ga element, Fe element and K element.

[0065] In the present invention, the general formula is Na x Fe[Fe(CN)6], where 1.8≤x<2.2 Prussian white material, from the perspective of optimizing the synthesis method, adopts low-cost sodium citrate (chelating agent) assisted co-precipitation method, which can effectively reduce the nucleation rate, inhibit lattice defects, improve crystal quality and improve electrochemical performance.

[0066] In the present invention, Na x Zr 2-y M y Si u P v O 12 The advantage of using at least one of Zn, Mg, Cu, Al, Ni, Ga, Fe and K in M ​​is to replace the high-valent elements in NASICON with low-valent elements, and introduce Na to achieve charge balance. + ,Na + The increase in concentration leads to an increase in ionic conductivity. In addition, by doping elements to regulate the skeleton structure on the sodium ion transmission path, the size of the transmission "bottleneck" (that is, the place where the ion transition energy barrier is the highest) is expanded, the migration energy barrier is reduced, and the ionic conductivity is improved.

[0067] Furthermore, the raw materials for preparing the Prussian white positive electrode also include a conductive agent, a binder and a high ion conductivity solid electrolyte;

[0068] The mass ratio of the Prussian white, the conductive agent, the binder and the high ion conductivity solid electrolyte is (70-80): (5-10): (5-20): (5-10).

[0069] Further, the conductive agent includes at least one of acetylene black, Ketjen black, carbon black, vapor-grown carbon fiber and carbon nanotubes;

[0070] The binder comprises at least one of polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene and sodium hydroxymethyl cellulose;

[0071] The high ionic conductivity solid electrolyte includes Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 and Na 3.4 Zr1.8 Cu 0.2 Si2PO 12 Any one of .

[0072] Based on the same inventive concept, the present invention provides a method for preparing a high-performance all-solid-state sodium ion battery, the preparation method comprising:

[0073] S1. Synthesis of Prussian white by coprecipitation method;

[0074] S2. The Prussian white, conductive agent, binder and high ionic conductivity solid electrolyte are dispersed in a solvent, applied on a current collector after grinding, and then dried to obtain a Prussian white positive electrode;

[0075] S3. The sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide are mixed and ball-milled, and the resulting slurry is dried and calcined to obtain a precursor powder;

[0076] S4. The precursor powder is ball-milled and dried, and then pressed and calcined to obtain a NASICON solid electrolyte;

[0077] S5. The Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery.

[0078] Step S1 specifically includes:

[0079] Dissolve sodium ferrocyanide in water to obtain solution A;

[0080] A soluble divalent transition metal salt is dissolved in water, and then a chelating agent is added to obtain a solution B;

[0081] Mixing the solution A and the solution B to perform a coprecipitation reaction to obtain a reaction solution;

[0082] The reaction liquid is subjected to solid-liquid separation, and the obtained solid is washed and dried to obtain Prussian white.

[0083] Furthermore, the soluble divalent transition metal includes ferrous salt, and the chelating agent includes sodium citrate.

[0084] In the present invention, the chelating agent has a strong chelating ability for transition metal ions. In the solution, the chelating agent will

[0085] [Fe(CN)6]4 –The ions compete with transition metal ions and coordinate with transition metal ions, thus hindering the spontaneous nucleation and precipitation of Prussian white to a certain extent. At the same time, the negatively charged ligand ions can also adsorb on the surface of the initial nucleus, thereby inhibiting the growth rate of the nucleus and preventing serious grain aggregation. Under these effects, the formed nuclei tend to grow into well-shaped dispersed particles with fewer defects.

[0086] Step S2 specifically includes:

[0087] The Prussian white, conductive agent, binder and high ion conductivity solid electrolyte are dispersed in N-methylpyrrolidone, ground evenly and coated on a current collector, and then dried to obtain a Prussian white positive electrode;

[0088] Wherein, the mass ratio of the Prussian white, the conductive agent, the binder and the high ion conductivity solid electrolyte is (70-80): (5-10): (5-20): (5-10);

[0089] The current collector comprises at least one of copper foil, aluminum foil, Al@C foil, titanium foil and stainless steel;

[0090] The conductive agent comprises at least one of acetylene black, Ketjen black, carbon black, vapor-grown carbon fiber and carbon nanotube;

[0091] The binder comprises at least one of polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene and sodium hydroxymethyl cellulose;

[0092] The high ionic conductivity solid electrolyte includes Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 and Na 3.4 Zr 1.8 Cu 0.2 Si2PO 12 Any one of .

[0093] Step S3 specifically includes:

[0094] Sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide are mixed and wet-milled with alcohol as the medium. The obtained slurry is dried and calcined at 1050-1200° C. for 7-10 hours to obtain a precursor powder.

[0095] Wherein, the molar ratio of the sodium carbonate, the zirconium dioxide, the silicon dioxide, the phosphate and the metal oxide is (3-4): (1.5-2): (1.8-2.5): (0.5-1.2): (0.1-0.4).

[0096] Step S4 specifically includes:

[0097] The precursor powder is ball-milled to a particle size of 1 to 5 μm, dried, pressed into sheets, and then calcined at 1050 to 1200° C. for 7 to 10 hours to obtain a NASICON solid electrolyte;

[0098] Wherein, the diameter of the NASICON type solid electrolyte is 6 to 15 mm, and the thickness is 0.6 to 2 mm.

[0099] Step S5 specifically includes:

[0100] The Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery, and the metallic sodium negative electrode is preheated to 100±15°C.

[0101] In the present invention, the purpose of preheating the metallic sodium negative electrode to 100±15° C. is to ensure close contact between the interfaces of each unit.

[0102] The following is a detailed description of a high-performance all-solid-state sodium ion battery and a preparation method thereof in combination with embodiments and experimental data.

[0103] Example 1

[0104] This embodiment provides a method for preparing a high-performance all-solid-state sodium ion battery, and the specific steps are as follows:

[0105] S1. Preparation of positive electrode: Prussian white material was synthesized by coprecipitation method: 4mmol Na4Fe(CN)6·H2O was dissolved in 200mL deionized water to form solution A, and 6mmol FeSO4·7H2O and 15g sodium citrate were dissolved in 200mL deionized water to form solution B. Then the mixture was mixed and stirred evenly, placed at room temperature for 12h and then aged for 24h, then the precipitate was centrifuged and washed with deionized water and anhydrous ethanol for several times to remove excess impurities, and finally placed in a vacuum drying oven at 100℃ for 24h to obtain Prussian white material Na2Fe[Fe(CN)6].

[0106] The above-mentioned Prussian white and the conductive agent Ketjen black powder, the binder polyvinylidene fluoride (PVDF), the high ion conductivity solid electrolyte Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P0.8 O 12 The mixture was mixed in a mass ratio of 7:1:1:1, and ground into a positive electrode slurry in an agate mortar with N-methyl-2-pyrrolidone (NMP) as solvent. The slurry was evenly coated on Al@C foil and dried at 80°C for 10 h to obtain a Prussian white positive electrode sheet.

[0107] S2. Preparation of solid electrolyte: Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and zinc oxide powders were weighed in a molar ratio of 3.4:1.9:2.2:0.8:0.1, mixed, and wet-milled with alcohol as a medium. The obtained slurry was dried and calcined at 1150°C for 8 hours to obtain a precursor powder; the precursor powder was wet-milled with alcohol as a medium, dried and tableted and calcined at a calcination temperature of 1200°C for 8 hours to obtain Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 Solid electrolyte sheet (diameter 10.23mm, thickness 1.09mm).

[0108] S3. Negative electrode preparation: remove the oxide on the surface of sodium, roll it into a thin sheet, and use a punch to obtain a metallic sodium disc as the negative electrode (diameter 9 mm, thickness 1 mm).

[0109] S4, preheat the negative electrode side sodium metal at 100°C, and follow the order of negative electrode shell-negative electrode-solid electrolyte-positive electrode-positive electrode shell (such as Figure 4 ), Prussian white positive electrode and Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The solid electrolyte sheet and the metallic sodium negative electrode form an all-solid-state battery (CR2032 button cell), and the entire assembly process is carried out in a glove box.

[0110] Figure 1 The obtained Prussian white X-ray diffraction pattern (left) and scanning electron microscope image (right). Figure 2 For the obtained Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 Solid electrolyte X-ray diffraction spectrum (left) and actual picture (right), Figure 3 To obtain Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8O 12 SEM image of solid electrolyte. Figure 4 Schematic diagram of the all-solid-state battery structure.

[0111] from Figure 1 As can be seen from the left figure: the present invention successfully synthesized the Prussian white material;

[0112] from Figure 1 As can be seen from the right figure: Prussian white material has a regular organizational structure, uniform size distribution, and small particle size;

[0113] from Figure 2 The left figure shows that: with Na3Zr2Si2PO 12 The standard card (ICSD NO.473) corresponds to that of the present invention, indicating that the NZSP electrolyte is successfully synthesized, and the appearance of Na3Zn3(PO4)5 proves that zinc is successfully doped;

[0114] from Figure 2 The right picture shows: Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The solid electrolyte sheet has a diameter of 10.23 mm and a thickness of 1.09 mm;

[0115] from Figure 3 It can be seen that: 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The solid electrolyte has fine grains, dense morphology and high sintering density.

[0116] Example 2

[0117] This embodiment provides sodium vanadium phosphate || Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 ||Na all-solid-state sodium ion battery, the specific steps are as follows:

[0118] S1. Preparation of positive electrode: Sodium vanadium phosphate material is synthesized by solution reaction method: 2.6g vanadium chloride is dissolved in 50mL deionized water to prepare solution A. Weigh 2.4g sodium hydroxide and dissolve it in 5mL deionized water to prepare solution B; then add solution B to solution A at a rate of one drop per second, stir continuously at room temperature until the solution pH = 7, and obtain the vanadium hydroxide precursor after centrifugal filtration. Weigh 1.2g sodium fluoride and 10.6g disodium hydrogen phosphate, dissolve in 50ml deionized water to prepare solution C. Disperse the obtained vanadium hydroxide precursor in solution C, stir continuously at room temperature for 12h, filter and dry to obtain the sodium vanadium phosphate material Na3V2(PO4)3;

[0119] The sodium vanadium phosphate and the conductive agent Ketjen black powder, the binder polyvinylidene fluoride (PVDF), the high ion conductivity solid electrolyte precursor Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The powders were mixed in a mass ratio of 7:1:1:1, ground into a positive electrode slurry in an agate mortar with N-methylpyrrolidone (NMP) as solvent, evenly coated on Al@C foil, and dried at 80°C for 10 h to obtain a positive electrode sheet.

[0120] S2. Preparation of solid electrolyte: Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The method for preparing the solid electrolyte sheet is consistent with step S2 of Example 1;

[0121] S3, negative electrode preparation: remove the oxide on the surface of sodium, roll it into thin sheets, and use a punch to obtain a metallic sodium disc as the negative electrode;

[0122] S4, preheat the negative electrode side sodium metal at 100 ° C, and place the sodium vanadium phosphate positive electrode and Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The solid electrolyte sheet and the metallic sodium negative electrode form an all-solid-state battery (CR2032 button cell), and the entire assembly process is carried out in a glove box.

[0123] Compared with Example 1, the preparation of sodium vanadium phosphate material involves multiple steps, the preparation method is complex, and the requirements for process and equipment are high, which increases the production cost and limits the possibility of large-scale production.

[0124] Example 3

[0125] This example provides Prussian white || Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 ||NaThe preparation method of all-solid-state sodium ion battery, the specific steps are as follows:

[0126] S1. Preparation of positive electrode: The preparation method of the Prussian white positive electrode sheet in this embodiment is consistent with step S1 of embodiment 1.

[0127] S2. Preparation of solid electrolyte: Sodium carbonate, zirconium dioxide, silicon dioxide, ammonium dihydrogen phosphate and magnesium oxide powders were weighed in a molar ratio of 3.25:1.875:2:1:0.125, mixed, and wet-milled with alcohol as a medium. The resulting slurry was dried and calcined at 1150°C for 8 hours to obtain a precursor powder; the precursor powder was wet-milled with alcohol as a medium, dried, pressed into tablets and calcined at a calcination temperature of 1200°C for 8 hours to obtain Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 Solid electrolyte sheet;

[0128] S3, negative electrode preparation: remove the oxide on the surface of sodium, roll it into thin sheets, and use a punch to obtain a metallic sodium disc as the negative electrode;

[0129] S4, preheat the negative electrode side sodium metal at 100 ° C, and place the Prussian white positive electrode and Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 The solid electrolyte sheet and the metallic sodium negative electrode form an all-solid-state battery, and the entire assembly process is carried out in a glove box.

[0130] The materials obtained from the above embodiments were subjected to the following performance tests:

[0131] 1. Ionic conductivity test

[0132] The Na prepared in Example 1 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The solid electrolyte ceramic sheet was surface polished, and then a dense layer of silver was coated on both sides as a blocking electrode. The AC impedance method was used to test the ionic conductivity of the solid electrolyte. Figure 5 for Na 3.4 Zr1.9 Zn 0.1 Si 2.2 P 0.8 O 12 Solid electrolyte impedance spectrum (left).

[0133] from Figure 5 From the left picture, we can see that: Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The total impedance of the solid electrolyte is 57.48Ω, and the Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The ionic conductivity of the solid electrolyte is 1.5 mS / cm.

[0134] 2. Electrochemical window test

[0135] The Na prepared in Example 1 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The solid electrolyte ceramic sheet was surface polished, and then a dense layer of silver was coated on the positive electrode side as a blocking electrode. Metal sodium was attached to the negative electrode side, and the electrochemical window of the solid electrolyte was tested using linear sweep voltammetry. Figure 5 for Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 Linear sweep voltammetry curve of solid electrolyte (right)

[0136] from Figure 5 The right picture shows: Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 The electrochemical window of the solid electrolyte is 5.2V.

[0137] 3. Full battery performance test

[0138] The Prussian white prepared in Example 1 || Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12||Na All-solid-state sodium ion battery and sodium vanadium phosphate prepared in Example 2 ||Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 ||Na all-solid-state sodium ion battery was charged and discharged at room temperature with a current density of 100mA / g. Figure 6 On the left is Prussian White || Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 ||Na all-solid-state sodium ion battery charge and discharge curve diagram, the results show that the Prussian white ||Na prepared in Example 1 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 ||Na all-solid-state sodium-ion battery has a first-cycle discharge capacity of 119 mAh g at room temperature -1 , ( Figure 6 Right) is sodium vanadium phosphate

[0139] ||Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 ||Na charge and discharge curve of all-solid-state sodium ion battery. The results show that sodium vanadium phosphate prepared in Example 2 ||Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 ||Na all-solid-state sodium ion battery has a first cycle discharge capacity of 60 mAh g at room temperature -1 .

[0140] Figure 7 Prussian White || Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 ||Na all-solid-state sodium ion battery cycle performance diagram, the results show that the Prussian white prepared in Example 1 ||Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12||NaAfter 1000 cycles at room temperature, the capacity retention rate of all-solid-state sodium-ion batteries can reach 75% and the Coulomb efficiency is close to 100%.

[0141] The numerical range of the present invention includes not only the point values ​​listed in the above embodiments, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0142] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0143] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0144] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A high-performance all-solid-state sodium ion battery, characterized in that: The sodium ion battery comprises a Prussian white positive electrode, a metallic sodium negative electrode and a NASICON type solid electrolyte; The raw material for preparing the Prussian white positive electrode comprises Prussian white, and the general formula of the Prussian white is: Na x Fe[Fe(CN)6], where 1.8≤x<2.2; The composition of the NASICON solid electrolyte is Na x Zr 2-y M y Si u P v O 12 , where 0<x≤4, 0≤y<2, 0<u, v<3; The Na x Zr 2-y M y Si u P v O 12 Here, M is at least one of Zn element, Mg element, Cu element, Al element, Ni element, Ga element, Fe element and K element.

2. A high performance all-solid-state sodium ion battery according to claim 1, characterized in that: The raw materials for preparing the Prussian white positive electrode also include a conductive agent, a binder and a high ion conductivity solid electrolyte; The mass ratio of the Prussian white, the conductive agent, the binder and the high ion conductivity solid electrolyte is (70-80): (5-10): (5-20): (5-10).

3. A high performance all-solid-state sodium ion battery according to claim 2, characterized in that: The conductive agent comprises at least one of acetylene black, Ketjen black, carbon black, vapor-grown carbon fiber and carbon nanotube; The binder comprises at least one of polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene and sodium hydroxymethyl cellulose; The high ionic conductivity solid electrolyte includes Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 and Na 3.4 Zr 1.8 Cu 0.2 Si2PO 12 Any one of .

4. A method for preparing a high-performance all-solid-state sodium ion battery according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Prussian white was synthesized by coprecipitation method; The Prussian white, conductive agent, binder and high ion conductivity solid electrolyte are dispersed in a solvent, coated on a current collector after grinding, and then dried to obtain a Prussian white positive electrode; Sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide are mixed and ball-milled, and the obtained slurry is dried and calcined to obtain a precursor powder; The precursor powder is ball-milled and dried, and then tableted and calcined to obtain a NASICON solid electrolyte; The Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery.

5. The method for preparing a high-performance all-solid-state sodium ion battery according to claim 4, characterized in that: The coprecipitation method for synthesizing Prussian white specifically comprises: Dissolve sodium ferrocyanide in water to obtain solution A; A soluble divalent transition metal salt is dissolved in water, and then a chelating agent is added to obtain a solution B; Mixing the solution A and the solution B to perform a coprecipitation reaction to obtain a reaction solution; The reaction liquid is subjected to solid-liquid separation, and the obtained solid is washed and dried to obtain Prussian white.

6. The method for preparing a high-performance all-solid-state sodium ion battery according to claim 5, characterized in that: The soluble divalent transition metal comprises a ferrous salt, and the chelating agent comprises sodium citrate.

7. The method for preparing a high-performance all-solid-state sodium ion battery according to claim 4, characterized in that: The Prussian white, conductive agent, binder and high ion conductivity solid electrolyte are dispersed in a solvent, coated on a current collector after grinding, and then dried to obtain a Prussian white positive electrode, which specifically includes: The Prussian white, conductive agent, binder and high ion conductivity solid electrolyte are dispersed in N-methylpyrrolidone, ground evenly and coated on a current collector, and then dried to obtain a Prussian white positive electrode; Wherein, the mass ratio of the Prussian white, the conductive agent, the binder and the high ion conductivity solid electrolyte is (70-80): (5-10): (5-20): (5-10); The current collector comprises at least one of copper foil, aluminum foil, Al@C foil, titanium foil and stainless steel; The conductive agent comprises at least one of acetylene black, Ketjen black, carbon black, vapor-grown carbon fiber and carbon nanotube; The binder comprises at least one of polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene and sodium hydroxymethyl cellulose; The high ionic conductivity solid electrolyte includes Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.25 Zr 1.875 Mg 0.125 Si2PO 12 and Na 3.4 Zr 1.8 Cu 0.2 Si2PO 12 Any one of .

8. The method for preparing a high-performance all-solid-state sodium ion battery according to claim 4, characterized in that: The method comprises mixing sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide and then ball milling the mixture, and then drying and calcining the obtained slurry to obtain a precursor powder, which specifically comprises: Sodium carbonate, zirconium dioxide, silicon dioxide, phosphate and metal oxide are mixed and wet-milled with alcohol as the medium. The obtained slurry is dried and calcined at 1050-1200° C. for 7-10 hours to obtain a precursor powder. Wherein, the molar ratio of the sodium carbonate, the zirconium dioxide, the silicon dioxide, the phosphate and the metal oxide is (3-4): (1.5-2): (1.8-2.5): (0.5-1.2): (0.1-0.4).

9. The method for preparing a high-performance all-solid-state sodium ion battery according to claim 4, characterized in that: The precursor powder is ball-milled and dried, and then pressed and calcined to obtain a NASICON solid electrolyte, which specifically includes: The precursor powder is ball-milled to a particle size of 1 to 5 μm, dried, pressed into sheets, and then calcined at 1050 to 1200° C. for 7 to 10 hours to obtain a NASICON solid electrolyte; Wherein, the diameter of the NASICON solid electrolyte is 6 to 15 mm, and the thickness is 0.6 to 2 mm.

10. The method for preparing a high-performance all-solid-state sodium ion battery according to claim 4, characterized in that: The Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery, specifically comprising: The Prussian white positive electrode and the metallic sodium negative electrode are stacked on both sides of the NASICON type solid electrolyte to obtain a high-performance all-solid-state sodium ion battery, and the metallic sodium negative electrode is preheated to 100±15°C.

Citation Information

Cited By

  • Prussian white-based halide-based high-performance sodium ion battery and preparation method thereof

    CN120165058A

  • Composite ceramic electrolyte, all-solid-state sodium battery and preparation method and application of all-solid-state sodium battery

    CN121292963A

  • Composite ceramic electrolyte, all-solid-state sodium battery and preparation method and application thereof

    CN121292963B

  • Sodium ion solid electrolyte material with two-phase structure as well as preparation method and application of sodium ion solid electrolyte material

    CN122118052A